The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1149/2.024301jss
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Assisted Atomic Layer Deposition of SrTiO3: Stoichiometry and Crystallinity Studied by Spectroscopic Ellipsometry

Abstract: Strontium titanate (SrTiO3, STO) films were deposited by plasma-assisted ALD using cyclopentadienyl-based Sr- and Ti-precursors with O2 plasma as the oxidizing agent. Spectroscopic ellipsometry (SE) was employed to determine the thickness and the optical properties of the layers. As determined from Rutherford backscattering spectrometry (RBS), [Sr]/([Sr]+[Ti]) ratios ranging from 0.42 to 0.68 were achieved for 30–40 nm thick films by tuning the [SrO]/[TiO2] ALD cycle ratio. Films deposited at 250°C were amorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 38 publications
6
30
0
Order By: Relevance
“…The elemental composition was extracted from the ellipsometry data by means of an optical constant library which was calibrated by means of Rutherford backscattering experiments. 21 The Table I. RTA in flowing N 2 was performed in an AST SHS100 system at temperatures ranging from 550…”
Section: Methodsmentioning
confidence: 99%
“…The elemental composition was extracted from the ellipsometry data by means of an optical constant library which was calibrated by means of Rutherford backscattering experiments. 21 The Table I. RTA in flowing N 2 was performed in an AST SHS100 system at temperatures ranging from 550…”
Section: Methodsmentioning
confidence: 99%
“…In their work, Niinist€ o et al showed a similar temperature dependence of the HfO 2 film crystallinity with a clear transition from amorphous to crystalline films at a deposition temperature of 300 C. The difference in temperature between this work and the one reported by Niinist€ o et al at which this transition could be observed is imputed to a $20%-25% difference between the set stage temperature value and the actual substrate temperature for the reactor employed in this work. 32 It can be concluded that the crystallization temperature of HfO 2 films is rather independent of the oxygen source used in combination with HfCp(NMe 2 ) 3 during the ALD process. However, the usage of a plasma-assisted ALD process may open the possibility for tuning of the crystalline phase by ion bombardment by employing substrate biasing during processing, 33 which is the object of further investigation.…”
Section: B Optoelectronic Properties and Crystallinitymentioning
confidence: 97%
“…Further details on the growth process can be found in recent publications. 23,27 For the use as bottom electrode, the Pt film is structured into 100 nm wide bars by means of nanoimprint lithography and reactive ion beam etching (RIBE). The resistive switching cell is completed by a 30 nm TiN film, deposited by sputtering, and capped with a Pt layer.…”
Section: Introductionmentioning
confidence: 99%